Systematic Mapping Study of Academic Engagement in MOOC - Guajardo Leal, Brenda Edith; Navarro-Corona, Claudia; Valenzuela González, Jaime Ricardo (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2019)
MOOCs are presented as an affordable and easily accessible modality that offers the opportunity to democratize education in our time; however, this convenience training favors a low completion rate of the participants. Faced with this situation, scholars have suggested that it is necessary to deepen the construct of academic engagement, a concept that has been addressed in the study of face-to-face training, to better understand how students participate in this educational modality. This article systematically explores the existing literature, in the period of 2015-2018, about the construct of academic engagement in online, massive and open learning courses, through a Systematic Mapping of Literature, a method which aims to identify the characteristics of production in a given subject. The results show that there is a considerable increase in published articles that associate academic engagement and MOOCs, mainly from the United States, Australia, and the United Kingdom. Most of the mapped publications employ qualitative methods, with an exploratory approach, although there are several correlational studies. The study of participation patterns and instructional design appear as the main topics of interest in the field. In addition to providing a general overview of production on the subject, the research provides accurate information that will identify works for more in-depth reviews. Thus, it also offers a replicable and flexible literature search method for different research interests.